DEBIT ALIRAN (WATER YIELD) SUB-DAS CIGUMENTONG DAN CIMULU SUB-DAS CITARIK BAGIAN PALING HULU - Haryanto, Edi Tri; Nur, Andi Agus; Haryanto, Iyan; Yuniardi, Yuyun (Bulletin of Scientific Contribution, 2015)
Cigumentong and Cimulu sub-watersheds are growing at vokanik denudasional landform with geological formations of undeferienciated old volcanic product consists of tuff , breccia and lava of the uppermost of Citarik Sub-Catchment . Based on the order system according to Strahlaar both river is a river -order 4 , with the land cover of relatively dense forest vegetation with an area of 552 Ha respectively and 606 Ha . This study aims to investigate the flow discharge characteristics of the two rivers by measuring daily and daily rainfall during the period 20 December 2014 through to March 2015, or for 71 days . The research result is fluctuations in flow discharge rate between the River Cigumentong and Cimulu tend to be similar . Inlfiltration coefficient of Cimulu sub-watersheed was slightly larger (0.54)than that was Cigumentong sub-watersheed (0.53), with the infiltration thickness of 695 mm for Cimulu and 577 mm for Cigumentong. Runoff coefficient Cimulu sub-watersheed is larger (0.44) than Cigumentong (0.37) .